Only One Science Twelfth Annual Report of the National Science Board. - National Science Foundation, Washington, DC. National Science Board; National Science Foundation, Washington, DC. National Science Board ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Departing markedly from previous reports to Congress by the National Science Board, this document presents in an informal, narrative style six stories depicting scientific discoveries and their effects on society. Drawn from the physical, biological, medical, and social sciences, topics discussed include: (1) computers and semiconductors; (2) seismic exploration for oil and gas; (3) survey research and opinion polls; (4) pesticides and pest control; (5) synthetic fibers; and (6) x-rays for medical diagnosis. Each chapter examines the technological, social, and political aspects of these current issues and illustrates how major scientific developments most often emerge from the combined efforts of individuals, universities, industries, and government. Illustrations and photographs complement the text. The publication is not intended as a policy or budgetary guide but as an example of the interrelationship between science and the general welfare of society. (DC)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computers; Environmental Education; Federal Programs; Medical Research; Medicine; Natural Sciences; Pesticides; Radiology; Science Education; Scientific Enterprise; Scientific Research; Seismology; Semiconductor Devices; Social Sciences; Surveys; Technology; Science and Society; National Science Foundation; Reports, Descriptive